Hacks. Season two [videorecording (DVD)] - Aniello, Lucia; Downs, Paul W.; Statsky, Jen, 1985- (2022)
Multiple Emmy Award winner Jean Smart stars as a legendary Las Vegas comedian who is forced to hire an ambitious young writer. These two talented comedic voices from different generations form an unlikely bond in this new comedy from "Broad City" alums Paul W. Downs, Lucia Aniello and Jen Statsky and Emmy Award winning executive producer Michael Schur.